2015
DOI: 10.1021/jm501565k
|View full text |Cite
|
Sign up to set email alerts
|

Nitrocobinamide, a New Cyanide Antidote That Can Be Administered by Intramuscular Injection

Abstract: Currently available cyanide antidotes must be given by intravenous injection over 5–10 min, making them illsuited for treating many people in the field, as could occur in a major fire, an industrial accident, or a terrorist attack. These scenarios call for a drug that can be given quickly, e.g., by intramuscular injection. We have shown that aquohydroxocobinamide is a potent cyanide antidote in animal models of cyanide poisoning, but it is unstable in solution and poorly absorbed after intramuscular injection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 47 publications
1
47
0
Order By: Relevance
“…The affinity (K a ) of each of these three ligands for cobinamide is very different, ranging over a large log scale: K a overall for cyanide is ~ 10 22 M −2 , K a for sulfite is ~ 10 11 M −1 , and K a overall for nitrite is ~ 10 5 M −2 [overall affinity includes the affinity for each of the two cyanide and nitrite ligands [16]. Thus, cobinamide very readily binds cyanide, becoming saturated with two cyanide groups even at a relatively low cyanide to cobinamide ratio, whereas a much higher nitrite to cobinamide ratio is required to saturate cobinamide with two bound nitrite groups [17]. Saturation with sulfite is intermediate to that of cyanide and nitrite.…”
Section: Methodsmentioning
confidence: 99%
“…The affinity (K a ) of each of these three ligands for cobinamide is very different, ranging over a large log scale: K a overall for cyanide is ~ 10 22 M −2 , K a for sulfite is ~ 10 11 M −1 , and K a overall for nitrite is ~ 10 5 M −2 [overall affinity includes the affinity for each of the two cyanide and nitrite ligands [16]. Thus, cobinamide very readily binds cyanide, becoming saturated with two cyanide groups even at a relatively low cyanide to cobinamide ratio, whereas a much higher nitrite to cobinamide ratio is required to saturate cobinamide with two bound nitrite groups [17]. Saturation with sulfite is intermediate to that of cyanide and nitrite.…”
Section: Methodsmentioning
confidence: 99%
“…Dinitrocobinamide was prepared from hydroxocobalamin as previously described [20]. Aquohydroxocobinamide was prepared from dinitrocobinamide by reducing the cobalt atom to the +1 valency state using sodium borohydride; this simultaneously removes nitrite from cobinamide and reduces nitrite to nitric oxide.…”
Section: Data Collectionmentioning
confidence: 99%
“…We have shown that both aquohydroxocobinamide (water and hydroxyl molecules bound to the cobalt atom) and dinitrocobinamide (two nitrite groups bound to the cobalt atom) are effective cyanide antidotes [12,15,17,20] (Fig. 1).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations